Effects of leukemia inhibitory receptor gene mutations on human hypothalamo-pituitary-adrenal function - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (SPRINGER, 2015)
Stuve-Wiedemann syndrome (STWS) (MIM #601559) is a rare autosomal recessive disorder caused by mutations in the leukemia inhibitory factor receptor (LIFR) gene. STWS has a diverse range of clinical features involving hematopoietic, skeletal, neuronal and immune systems. STWS manifests a high mortality due to increased risk of sudden death. Heterodimerization of the LIFR mediates leukemia inhibitory factor (LIF) signalling through the intracellular Janus kinase (JAK)/STAT3 signalling cascade. The LIF/LIFR system is highly expressed in and regulates the hypothalamo-pituitary-adrenal (HPA) axis. HPA function was investigated in three STWS patients to characterise consequences of impaired LIF/LIFR signalling on adrenal function. Six genetically proven STWS patients from four unrelated Turkish families were included in the study. Sudden death occurred in three before 2 years of age. Basal adrenal function tests were performed by measurement of early morning serum cortisol and plasma ACTH concentrations on at least two different occasions. Low dose synacthen stimulation test and glucagon stimulation tests were performed to explore adrenal function in three patients who survived. All patients carried the same LIFR (p.Arg692X) mutation. Our oldest patient had attenuated morning serum cortisol and plasma ACTH levels at repeated measurements. Two of three patients had attenuated cortisol response (< 18 mu g/dl) to glucagon, one of whom also had borderline cortisol response to low dose (1 mu g) ACTH stimulation consistent with central adrenal insufficiency. STWS patients may develop central adrenal insufficiency due to impaired LIF/LIFR signalling. LIF/LIFR system plays a role in human HPA axis regulation.
Keywords: LIFR; Stuve-Wiedemann; Hypothalamo-pituitary-adrenal; JAK-STAT; FACTOR LIF; EXPRESSION; CHILDREN; STEROIDOGENESIS; HORMONE; ACTH; AXIS; INSUFFICIENCY; TRANSCRIPTION; ACTIVATION